2021
DOI: 10.3389/fmed.2021.585851
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Low-Density Lipoprotein Cholesterol Level Indicates Poor Prognosis of Severe and Critical COVID-19 Patients: A Retrospective, Single-Center Study

Abstract: Coronavirus disease 2019 (COVID-19) has become a global public health crisis. Reduced low-density lipoprotein cholesterol (LDL-C) levels were observed in COVID-19 patients. The present study aimed to explore the relationship between LDL-C levels and the prognosis of severe and critical COVID-19 patients. A total of 211 severe and critical COVID-19 patients were enrolled and divided into four groups according to the LDL-C levels, including 53 patients in Group A (LDL-C ≥ 2.71 mmol/L), 53 patients in Group B (2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 40 publications
2
17
0
1
Order By: Relevance
“…The observed positive association between TC and LDL-C reduction over the acute phase of COVID-19 and either CRP levels or COVID-19 severity at hospital admission is in line with the results of previous studies having shown lower TC and LDL-C levels in COVID-19 patients with a higher inflammatory burden and more severe clinical manifestations [ 8 , 31 , 32 ]. To date, several pathophysiological mechanisms have been proposed to explain the reduction of TC and LDL-C levels during the acute phase of COVID-19 in parallel with the increase of inflammatory biomarkers and disease severity.…”
Section: Discussionsupporting
confidence: 91%
“…The observed positive association between TC and LDL-C reduction over the acute phase of COVID-19 and either CRP levels or COVID-19 severity at hospital admission is in line with the results of previous studies having shown lower TC and LDL-C levels in COVID-19 patients with a higher inflammatory burden and more severe clinical manifestations [ 8 , 31 , 32 ]. To date, several pathophysiological mechanisms have been proposed to explain the reduction of TC and LDL-C levels during the acute phase of COVID-19 in parallel with the increase of inflammatory biomarkers and disease severity.…”
Section: Discussionsupporting
confidence: 91%
“…The possible mechanisms include liver damage, acute inflammation, increased free radicals, and changes in vascular permeability 64 . Compared with patients with high LDL-C levels, patients with low LDL-C levels are more likely to have immune and inflammatory dysfunction, renal dysfunction, liver dysfunction, and cardiac insufficiency on admission 118 . It is still uncertain whether the secondary hypocholesterolemia of COVID-19 patients will participate in other pathophysiological mechanisms that are not conducive to the prognosis 119 , so the lipid-lowering goal for COVID-19 patients may not be as low as possible.…”
Section: Inspiration For Treatmentmentioning
confidence: 99%
“…STRA6 mediates cellular uptake of retinol by binding with the retinol-coupled RBP molecule to trigger the release and internalization of retinol, in addition to cholesterol uptake into human cells (53). It has been shown that both retinol and cholesterol decrease in COVID-19 infection (54,55,56,57). STRA6 is at the center of a complex signaling network and plays a key role (58,59).…”
Section: Stra6 Receptors and Retinoid Signaling Disorder In The Patho...mentioning
confidence: 99%